Studi Fenomenologis : Perilaku adaptif karyawan lembaga keuangan mikro dimasa pandemi - Dhiyan Septa Wihara (AKUNTABILITAS: Jurnal Ilmiah Ilmu-Ilmu Ekonomi, 2020)
This study aims to examine and analyze in depth the adaptive behavior of employees of microfinance institutions, especially rural banks and cooperatives during the Covid-19 pandemic. This adaptive behavior is divided into 4, namely building communication with customers, getting used to new conditions, socializing and getting along with the community, continuing to move to meet targets. The phenomenological study is used because this data comes from the experience of participants who are currently active leaders in microfinance institutions. This study used 2 participants, namely the head of the BPR branch and the manager of a savings and loan cooperative, both of whom have decades of experience in microfinance institutions. The research findings show that the way to adapt in the midst of a pandemic to collect is by changing your appearance by not wearing uniforms and shoes when visiting customers. Then employees must also familiarize themselves with implementing the Covid protocol at work. The office provides hand washing facilities and handsanitazers for customers and employees, and this will have to be used later. Reporting on the results of performance limitations is carried out once a month but the policy for employees is focused on billing activities because it is to reduce risk.